Reflection on: “The Power and Paradoxes of Evaluation Systems – Increasing Use but Impeding Change” - Magdalenić, Sanja (Scandinavian Journal of Public Administration, 2021)
For me, evaluation is a fascinating field full of paradoxes and I welcome the fact that the article draws attention to the power and paradoxes of evaluation systems. The reflections that follow, rooted in the Swedish context, come from a PhD in sociology who has learned to love evaluation. I am privileged in that I can move across the Swedish evaluation landscape and its various fields of play such as academia, the Swedish Evaluation Society (SVUF) and the arenas that evaluation researchers tend to call “practice”. Here are my thoughts, sparked by the article, on contestability differential, evaluation systems, the paradox of epistemological coherence and the ways forward.